Who gets counted? Understanding low female death registration in India - Sheetal Verma; Ritul Kamal; Laxmi Kant Dwivedi; Mrigesh Bhatia (PLoS ONE, 2025)
Background Civil Registration and Vital Statistics (CRVS) systems are essential for governance, public health, and achieving SDGs however, gender gaps limit women’s access to rights and services, with under-registration of female vital events reinforcing their invisibility and distorting gender-responsive policies. Objectives This study examines the drivers of low female death registration across India’s States and Union Territories, focusing on the roles of age, gender and wealth, with an aim to inform policies to strengthen CRVS systems and reduce gender disparities in vital statistics. Methods The study utilizes data from NFHS-5 (2019–2021 for examining the factors associated with female death registration. Multivariable logistic regression models have been used to examine the impact of socio-economic and demographic factors on female death registration in India. Findings The results highlight a significant gender gap in death registration (73% male vs. 64% female). The gap is widest in states like Bihar and Uttar Pradesh, while states like Kerala and Goa report near universal registration for both sexes. Gender gaps in housing and land ownership align with gaps in death registration, suggesting a strong association between asset ownership and registration. The results highlight association between wealth and death registration, with rates rising across quintiles for both sexes; however males consistently have higher registration rates. Among the poorest, the gap is widest which narrows down in the richest group. A gender gap in death registration persists across all age groups in India, beginning early, widening during working ages, and continuing into old age; while registration rates improve with age and wealth, women especially among the poorest remain under-registered, particularly in early and later life stages. Conclusions Women in India encounter barriers to civil registration, and improving death registration demands systemic reforms, digital advancements, and community engagement Strengthening political commitment, collaboration, and public awareness will ensure inclusive, accurate records, enhancing CRVS for governance and policy.